The McFarland baseball quotations dictionary - Nathan, David H., 1967- (McFarland & Co., 2011)
"Back again, for a third edition, this compendium of the greatest baseball quotes of all time brings both the wisdom of the world and the bull of the bullpen. Organized by theme, the more than 5,800 quotations include the date, team, position and historical background when available"--Provided by publisher